Promoting coping competence for psychological stressors in nursing training: a controlled pedagogical intervention - Warwas, Julia; Krebs, Philine; Vorpahl, Wiebke; Weyland, Ulrike; Wilczek, Larissa; Seeber, Susan; Wittmann, Eveline (Frontiers in Medicine, 2024)
Multiple stressors as well as the health- and quality-impairing effects of strain in nursing require the systematic acquisition of competence in dealing with stressors, starting at the stage of initial vocational training. The study investigates whether an instructional concept, which merges didactic principles of nursing education with concepts and training measures from stress psychology, promotes the acquisition of stress coping competence more effectively than regular teaching on the relevant curricular field at nursing schools. The quasi-experimental study design, based on the Solomon four-group plan, included 332 trainees. The assessment of stress coping competence at the beginning and at the end of the intervention provided a video-stimulated situational judgment test covering nursing-specific stressful situations that were validated by field experts. Complementing group comparisons, regression analyses examined intervention effects at the individual level while controlling for other predictors of learning success. The highest solution rates with regard to the two basic competence dimensions of (1) situation assessment and (2) strategy selection and justification occurred in the treatment classes without a pretest. At the individual level, treatment effects were confirmed for the first dimension. Students with a migration background achieved lower competence gains than other students. Both the instructional approach and the competence test provide valuable foundations for the promotion and diagnosis of stress coping skills. Nevertheless, subsequent studies should examine adaptive support for different learner groups and, further, include observational phases that focus on the deliberate practice of acquired coping strategies in the practical training settings of nursing education.